Mechanism Of Pollination In Tribulus Terrestris L. (Zygophyllaceae) - SHOWKAT AHMED GANAIE (International Journal of Pharma and Bio Sciences, 2011)
Orange yellow coloured flowers of Tribulus terrestris L. have been studied for its pollination biology at Agra region. Mode of pollination indicated that T. terrestris was both self and cross pollinated as there was fruit-set in bagged inflorescence. The potential of the self-pollination was found to be 100% seed-set. Cross-pollination was achieved by both geitonogamy and xenogamy. The fruit formation was not merely dependent on the formation of viable gametes, but also on primary attractants (pollen and nectar) and secondary attractants (orange – yellow colour, odour, small size and fully open architecture and high floral density) that influenced visitors and brought out reproductive success. Honey bees Apis spp. and butterflies pieris and limenitis sps. were found to be the most efficient pollinators during the entire flowering period.